PENGARUH PENDIDIKAN DAN PELATIHAN, MODAL SOSIAL TERHADAP KEPUASAN KERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA BIRO UMUM BAGIAN KESEKRETARIATAN SEKRETARIAT DAERAH PROVINSI JAWA TENGAH) - 10.42.02.0115, Dina Adhiawati (Jurnal Mahasiswa Pasca Sarjana, 2013)
The purpose of this study to examine the influence of education and training, social capital and organizational commitment to employee job satisfaction Secretariat General Affairs Section Regional Secretariat of Central Java Province. To examine the effect of organizational commitment mediates the influence of education and training in employee job satisfaction and organizational commitment mediates the effect of social capital on job satisfaction of employees of General Affairs Section Regional Secretariat of Central Java Province.In this study population used is the General Affairs Section Secretariat of Central Java province, amounting to 130 people. The samples are part of the population that is used as an object of research headcount above 130 people. The determination of the number of samples by using purposive sampling technique sapling which means sampling based on certain criteria that an employee who has a minimum term of 5 years . Based on these criteria produced a sample of 110 respondents.Pursuant to result of research which have been conducted by hence can know by training and education have an effect on positive to organizational commitment. Social capital have an effect on to organizational commitment. Training education have an effect on positive to satisfaction of job. Social capital have an effect on to satisfaction of job. Organizational Commitment have an effect on to satisfaction of job. Organizational Commitment do not education mediate and training to satisfaction work because indirect influence smaller than at direct influence. Organizational Commitment do not social capital mediate to satisfaction work because indirect influence smaller than at direct influence. Keywords : Education and training, social capital, organizational commitment and job satisfaction